Hidrogéis baseados em goma arábica e guar: síntese e aplicação na remoção de corantes e estudo de liberação controlada de fármaco. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Hydrogels (HG) are three-dimensional polymeric networks capable of absorbing a large amount of water or other fluids. They can be synthesized from different polymers, synthetic or natural, such as gum arabic (GA) and guar gum (GG). Hydrogels have been studied for applications in areas such as pharmaceutical and environmental. Based on this, this work has two main objectives, to synthesize hybrid hydrogels based on gum arabic and pinion shell bran and apply them in the methylene blue dye (AM) removal process and to study the pH responsive behavior and the process of controlled release of hydrocortisone (HCS) from guar gum-based hydrogels in gastric fluid (FGS) and simulated in-testinal fluid (FIS). Initially, hybrid hydrogels were synthesized by 32 factorial design, using different amounts of GAm (250.0, 400.0 and 550.0 mg), ie GA modified with the crosslinking agent glycidyl methacrylate (GMA), and of pinion shell bran (0.0, 50.0 and 100.0 mg), together with constant amounts of N,N-dimethylacrylamide (DMAAm) and sodium acrylate (NaAc), obtaining 9 different formulations. Once obtained and dehydrated, the HGs’ swelling degree (GI) in aqueous solution was studied, measuring the water mass, in grams, absorbed per dried hydrogel gram, at specific time intervals over 168 hours. In this way, it was possible to verify that some formulations of the hybrid hydrogel showed a superabsorbent behavior (GI values above 100.0 g g-1), highlighting the HG called G2P2, composed with 400.0 mg of GAm and 50.0 mg of pinion shell bran (GI = 256.14 g g-1). Regarding the swelling mechanism, it was found that all formulations studied presented values for the diffusion exponent (n) consistent with anomalous transport. Statistical analyzes confirmed that there is a synergistic effect between GAm and pinion shell bran concentrations that affect the swelling properties of hybrid hydrogels. For the methylene blue removal tests (20.0 mg L-1), it was verified that the G2P2 and G2P3 hydrogels, containing 50.0 and 100.0 mg of the pinion shell bark, if previously swollen in water, showed greater dye removal capacity, reaching values close to 90%. Furthermore, hydrogels containing 100.0 mg of pinion shell bran demonstrated greater capacity for reuse as they maintained removal rates above 90% even after three cycles of use, suggesting a possible efficiency in removing methylene blue dye in concentrations above 20.0 mg L-1. For the controlled drug release studies, hydrogels produced by 22 factorial design from GG modified with GMA (7.32 mg L-1) and NaAc (1.0 and 2.0 g) and DMAAm (1.0 and 2.0 mL). The loading of hydrogels with HCS was carried out by swelling in an aqueous solution of the drug at a concentration of 40.0 g L-1, where the HG called G2A2D2, containing in its formulation the highest concentrations of NaAc and DMAAm, obtained the highest absorption (2585.6 g of HCS per gram of dried hydrogel). This result can be related to its higher GI value (22.2 ± 0.3 g g-1), in relation to the other GHs studied and its high porosity. This behavior was attributed to the ionized carboxyl groups of NaAc in the pH range close to 7.0, which generate electrostatic repulsion forces between the polymer chains, facilitating the swelling and absorption of HCS. For this same reason, HG G2A2D2 also had the highest drug release rate (1986.5 g g-1 or 77%) in release assays conducted in gastric (pH 1.2) and intestinal (pH 6,8) fluid simulated, revealing a pH responsive behavior, where greater control of the drug release process was observed in the intestinal fluid.
Keywords: hidrogel; goma arábica; goma guar; azul de metileno; hidrocortisona; hydrogel; arabic gum; guar gum; methylene blue dye; hydrocortisone; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA